The impact of brain imaginingon the accuracy of free throw skill in basketball - SABAH JASIM, YASAR (International Journal of Psychosocial Rehabilitation, 2020)
This study contains five chapters. Chapter one tackles the introduction of the study and the importance of the study, which emphasizes brain imaging, relaxation, and mind training. They influence positively and have an important role in developing basketball skills in general and the free throw skill in a specific way. Thus, trainers have to add it in their training units. The aim of the study is to know the relation between brain imaging and free throws in basketball and to know the influence of developing brain imaging on the accuracy of shooting in basketball. While the domains of the study contain the human domain, the players of sub-minion of basketball in Diyala who are 20. The place domain is the playground of the physical college. And the time domain is from the 2nd of Dec. 2004 until the 5th of Mar. 2005. The study also contains a review of the literature, method, and field procedures of the study; thus, the training method used for the sample chapter four contains displaying and analyzing results. Eventually, chapter five contains the conclusions, such as: mind training has a positive effect on learning shooting and free throws in basketball; moreover, mind training increases the possibility of success of free throws. Whereas the recommendations are using and emphasizing mind training for the trainers and players and emphasizing brain imaging and giving some time for it in the training unit and making a strategy to train the players to reinforce the skill aspect.